The Role of Proteoglycans in Contributing to Placental Thrombosis and Fetal Growth Restriction - Joanne M. Said (Hindawi Limited, 2011)
Fetal growth restriction is an important pregnancy complication that has major consequences for the fetus and neonate as well as an increased risk of long-term morbidity extending into adulthood. The precise aetiology of most cases of fetal growth restriction is unknown although placental thrombosis is a common feature in many of these cases. This paper will outline the potential role of proteoglycans in contributing to placental thrombosis and fetal growth restriction.